2002
DOI: 10.1182/blood.v99.9.3376
|View full text |Cite
|
Sign up to set email alerts
|

In situ localization of follicular lymphoma: description and analysis by laser capture microdissection

Abstract: From 1992 to 2000, we identified 23 lymph node biopsies with focal germinal centers (GCs) containing centrocytes staining strongly for bcl-2 protein, whereas most of the remaining lymph node showed bcl-2-negative follicular hyperplasia. We propose the designation in situ localization of follicular lymphoma (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
228
3
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(241 citation statements)
references
References 34 publications
7
228
3
3
Order By: Relevance
“…''In situ'' FL was originally described [3] as being one of the early events associated with FL development. The t(14;18)(q32;q21) translocation is the genetic hallmark and early initiating event of FL pathogenesis.…”
Section: Follicular Lymphomamentioning
confidence: 99%
See 2 more Smart Citations
“…''In situ'' FL was originally described [3] as being one of the early events associated with FL development. The t(14;18)(q32;q21) translocation is the genetic hallmark and early initiating event of FL pathogenesis.…”
Section: Follicular Lymphomamentioning
confidence: 99%
“…Among germinal center (GC)-derived lymphomas a type of follicular lymphoma (FL) has been described, in which t(14;18) positive and/or monoclonal B cells strongly expressing BCL2 are observed in histologically abnormal follicles in lymph node specimens from individuals without overt disease [1,3]. In the case of ''in situ'' FL, the accumulation of neoplastic cells is within the follicular GC only [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical studies for Bcl-2 protein had been performed at diagnosis on paraffin sections using previously published techniques. 22,23 Cases negative for Bcl-2 in paraffin sections were confirmed as negative in frozen sections. Nine cases were identified as negative for Bcl-2 protein.…”
Section: Case Selectionmentioning
confidence: 99%
“…More recently, it has been shown that some otherwise unremarkable lymph nodes with complete architectural preservation from patients without evidence of overt lymphoma can show BCL2-positive GCs that contain clonal B-cell populations and the IGH/BCL2 (Figure 3). [33][34][35] In some cases, only a few or even a single neoplastic GC may be present in the lymph node. These cases of so-called 'FL in situ' (also termed 'in situ involvement by FL-like cells' or 'FL-like B-cells of uncertain significance') are thought to represent the tissue equivalent of the rare circulating IGH/BCL2-positive cells detectable in normal peripheral blood.…”
Section: Precursor Lesion-'fl In Situ'mentioning
confidence: 99%